Monitoring of Evaporated Cooling Tower - K.Al-Dawery, Salam; K. H. Al-Mashhadani, Mahmood (Iraqi Journal of Chemical and Petroleum Engineering, 2009)
Thep resent study was conducted for monitoring of the evaporative cooling tower in methanol production plant using digital computer' visuql Basic computer program was used for the monitoring of the performance of the cooling tower. The structure program consists of sub programs and forms to show all the related variabltes such as temperature, flow rate, pressure ...etc, that affect the cooling tower operation and give alarms and important function informition regarding these variables.